Pengaruh Rotasi Audit, Audit Tenure dan Reputasi KAP Terhadap Kualitas Audit (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Muhammad Fajar Santosa; Maulana Malik Muhammad (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to examine the effect of audit rotation, audit tenure, and KAP reputation on audit quality. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The research sample was taken using purposive sampling technique and the number of samples in the study was 90 manufacturing companies so that the number of research observations was 270 observations. This study uses logistic regression analysis. The results of the conclusion conclude that audit rotation has a negative and significant effect on audit quality, audit tenure has no significant effect on audit quality and KAP's reputation has no significant effect on audit quality. on audit quality.